Analisis Minat Nasabah Dalam Memilih Produk Tabungan SI HASANAH Pada BMT Syariah Jaya Abadi Kecamatan Giri Mulya - Sylvina Intan Rahmawati; Miti Yarmunida; Herlina Yustati (UNIVED Press, 2023)
This study aims to determine the customer's interest in choosing the SI HASANAH savings product and the factors that influence the customer's interest in choosing the SI HASANAH savings product. This type of research is descriptive with a qualitative approach. With secondary data collection techniques sourced from books, journals, and other written sources as well as primary data, namely observations and interviews. The results showed that the customer's interest in choosing the SI HASANAH savings product at BMT Syariah Jaya Abadi, Giri Mulya District, was seen from the interest indicators as follows: a. Attention, b. Interest (Interest), c. Desire (desire), d. Action (Action). Meanwhile, the factors that influence customer interest in choosing SI HASANAH savings products at BMT Syariah Jaya Abadi, Giri Mulya District are: a. Convenience Factor, b. Promotion Factor, c. The friendliness factor, d. Trust Factor, e. Product Quality Factors, f. Religiosity Factor, g. Income Factor.